Testing and assessment for career guidance and counseling in school setting - Lau, Poh Li; Guan, Teik Ee; Ahmad Shamsuri bin Muhamad (2011)
Schools offer a transition to the job world so that the individual can contribute to peace and harmony in the family, society as well as the country. The career planning of individuals should start when they are in school because school is a place for developing talent, ability, potential and personality. Testing and Assessment is an important part for Career Guidance and Counselling in the school setting. Testing and assessment is essential in helping the career exploration process, especially in the process of self-understanding, to access the strengths and weaknesses, as well as to explore the potential of students. The use of psychological test enables the career counselor to gather useful information about the students and to help them in their career development especially in making career decisions. Assessment procedures used in career development programming and career counseling can be classified as objective, qualitative, and clinical. Objectives and qualitative assessment approaches are basic to career counseling and development. Clinical assessment is often based on a combination of objective and qualitative assessment as well as the counselor's hunches about the client. Throughout the history of the career counseling and development movement, objective or standardized tests have been emphasized. Schooling time is an important time for students start to decide on career matters. Thus, it can be said that the testing and assessment is a "tool" for the school counselor in career guidance and counseling.